2011
DOI: 10.1007/s11426-011-4441-5
|View full text |Cite
|
Sign up to set email alerts
|

Early stages of non-classic crystal growth

Abstract: Investigation of early stages of crystal growth revealed that crystal growth in some systems may not follow the classic route. In the early stages of inorganic crystal growth, precursor molecules and/or nanocrystallites may aggregate into large and disordered particles with the assistance of some polymers or biomolecules. Surface crystallization of these aggregates would then take place to form shells with high crystallinity and density, followed by an extension of the crystallization from surface to core. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The driving force for fusing the crystalline islands and eventually the formation of a single crystalline polyhedral shell with six {104} facets (Figure 7e), usually with an increase of reaction time, is said to be that to achieve a minimum surface free energy [70]. Reversed crystal growth examples have shown that surface re-crystallisation of the aggregates always leads to a polyhedral morphology with a minimised surface free energy even if the core region is disordered [48].…”
Section: Formation Mechanismmentioning
confidence: 99%
“…The driving force for fusing the crystalline islands and eventually the formation of a single crystalline polyhedral shell with six {104} facets (Figure 7e), usually with an increase of reaction time, is said to be that to achieve a minimum surface free energy [70]. Reversed crystal growth examples have shown that surface re-crystallisation of the aggregates always leads to a polyhedral morphology with a minimised surface free energy even if the core region is disordered [48].…”
Section: Formation Mechanismmentioning
confidence: 99%
“…We believe that the formation of chrysanthemum-shaped micron CaCO 3 may be firstly due to that the small water pools (we also call it droplets) gather around the carbon dioxide bubbles when carbon dioxide is bubbled into the microemulsion, and the carbon dioxide penetrated the small water pools combines with Ca 2+ to form nano CaCO 3 which has a similar size of the droplet. With continuous injection CO 2 continuously reacts with the surrounding microwater pools to form layers of nano CaCO 3 accumulations, just like the layered leaves of chrysanthemum, and the centre of the carbon dioxide bubble forms the stamens of chrysanthemum, and because of other factors, such as stirring, viscosity, temperature, pressure of carbon dioxide bubbles [44][45][46][47][48], etc. chrysanthemum-shaped micro-nano CaCO 3 was finally formed.…”
Section: Formation Mechanism Of Chrysanthemum-shaped Micron Cacomentioning
confidence: 99%
“…"Lichens are unique individuals which have been widely Heather F. Greer [16] Fengjiao Yu [16] Carol A. Fierke [18] Xiaomu Guan [18] Mina Han [27] Maria Luisa Cerón [30] Eleonora Echegaray [30] Bárbara Herrera [30] Soledad Gutiérrez-Oliva [30] Xiuting Li [31] Ada Yonath [34] Fang Liu [38] Figure 2 Photos of some female authors in the special issue on IYC 2011. used in traditional medicines," M. Iqbal Choudhary, Atta-ur-Rahman, and coworkers indicated [23]. They presented their findings of new antiglycation and enzyme inhibitors from the lichens species Parmotrema cooperi collected from Nepal at the altitude of 16001700 meters.…”
Section: Organic Biological and Polymeric Chemistrymentioning
confidence: 99%
“…Their article covers the preparation of SURMOFs, their growth mechanism, characterization methods, and applications [15]. Wuzong Zhou and coworkers discussed recent work in reversed crystal growth mechanism [16]. They have found that "in the early stages of inorganic crystal growth, precursor molecules and/or nanocrystallites may aggregate into large and disordered particles with the assistance of some polymers or biomolecules."…”
Section: Analytical Inorganic and Solid-state Chemistrymentioning
confidence: 99%